KAJIAN MANFAAT JALAN TRANS YAMDENA PADA JALUR DISTRIBUSI KOMODITI PERTANIAN DI KECAMATAN WERTAMRIAN KABUPATEN MALUKU TENGGARA BARAT (The Study of Trans Yamdena Road Benefits in Agricultural Commodities Distribution in Wertamrian District, Maluku Tenggara Barat Regency) - Melmambessy, Yesayas; Tulung, Max; Ngangi, Charles R. (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The study aims to examine the benefits of the Trans Yamdena Road as the main distribution channel for agricultural products, and to determine the distribution path of agricultural products before the opening of the Trans Yamdena Road in Wertamrian District, West Southeast Maluku Regency. The type of research data was qualitative. The data used in the study were secondary and primary ones. The secondary data were collected from the related sources according to the research objectives, and primary data were obtained directly from informants, which included farmers in Wertamrian District, the apparatus West Southeast Maluku Regency regional government, and Omele traditional market traders. Data were analyzed using Miles and Huberman models, and were tested by using triangulation methods. The results showed the benefits of the Trans Yamdena Road were ease of accessibility, creating business opportunities, transportation time and cost efficiency, expediting transportation and distribution processes of agricultural commodities, creating economic business opportunities and price stability, determining the location of economic center development, becoming the main supply channel for agricultural commodities. The study concluded that the benefits of the Trans Yamdena Road on the distribution channel of agricultural commodities in Wertamrian District were as supporting infrastructure for agricultural economic businesses, the main channel of distribution of agricultural commodities, and smoothing the supply chain. The distribution channel of agricultural commodities before the operation of the Trans Yamdena Road was the eastern sea lane, and the land area to the south of Yamdena Island.the Trans Yamdena Road is the eastern sea lane, and the land area to the south of Yamdena Island. Keywords: Benefits, Trans Yamdena Road, Social and Economy